Limit theorems for sums of random vectors combined into a non-homogeneous Markov chain. I - Raudeliūnas, A. (Lithuanian Mathematical Journal, 1961)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:A. Рауделюнас. Предельные теоремы для сумм случайных векторов, связанных в неоднородную цепь Маркова. IA. Raudeliūnas. Ribinės teoremos atsitiktinių vektorių, surištų į nehomogeninę Markovo grandinę, sumoms. I